Tinjauan Kasasi Penuntut Umum Atas Dasar Salah Menjatuhkan Sanksi Pidana Oleh Judex Factie Dalam Perkara Illegal Fishing - Setyono, Hanindito Arfebi (Sebelas Maret University, 2017)
This research aims to determine whether the submission of Cassation Prosecutor General with reasons Judex factie wrong to impose criminal sanctions in accordance with Article 253 Criminal Procedure Code. This type of research used by the authors to draw up legal research are doctrinal legal research. The author uses the approach of the case (case approach), that is by doing research on cases pertaining who already have permanent legal force. Legal materials analysis techniques used by the author is to use legal reasoning by deduction. The basis of this illegal fishing case, Judex Factie one drop criminal sanctions to the Defendant Jerry S. Deodor Philippine nationality who only gave sanction penalties imprisonment for 1 (one) year lighter than the primary demands of the Public Prosecutor, which is 3 (three) years, lighter prison where criminal sanctions will not provide a deterrent effect against perpetrators of illegal fishing areas of the Pacific Ocean fishery management area of the Republic of Indonesia. Not satisfied with the decision handed down by Judex factie, the Public Prosecutor fi led a cassation to the Supreme Court on the grounds Judex Factie any criminal sanctions and do not provide a deterrent effect to the perpetrators of the illegal fishing. For that reason, the Supreme Court granted the appeal filed Public Prosecutor. Based on research conducted by the author, the obtained results that associated with the submission of Cassation Public Prosecutor with reasons Judex Factie one drop criminal sanctions in the case of Illegal Fishing in accordance with the provisions contained in Article 253 paragraph (1) letter a Criminal Procedure Code. Keywords: Filing Cassation Public Prosecutor, misapply Sanctions Criminal, Illegal Fishing